Reforming of CO₂ -containing natural gas for synthesis gas production in low-temperature multistage gliding arc plasma system - Sumaeth Chavadej (Chulalongkorn University, 2010)
This project was financially supported by The Ratchada Pisak Sompot Fund, Chulalongkorn University